Project based learning framework integrating industry collaboration to enhance student future readiness in higher education - Fawad Naseer; Rasikh Tariq; Haya Mesfer Alshahrani; Nuha Alruwais; Fahd N. Al-Wesabi (Scientific Reports)
Abstract In the 21st -century, it is vital to prepare university students with the required skills to pursue them for future career success. The research presents a framework of project-based learning (PBL) enriched by the industry to increase students’ future readiness. The framework comprises collaboration with industry partners, solving real-world problems as projects, and interdisciplinary approaches intended to build specific critical skills like teamwork, problem-solving, and adaptability. The study investigates the impact of I-PBL methodologies and framework on higher education curricula to enhance the readiness of students for the future. The study focuses on two key parameters— (1) the percentage of the curriculum devoted to PBL and (2) the rate of industry engagement activities. The study examines how these educational methods prepare students for today’s workforce challenges. The study bridges quantitative outcomes, revealing how I-PBL enriched with industry engagement significantly enhance STEM students’ skills and readiness for the workforce. The quasi-experimental study quantitatively assessed the curriculum to determine the proportion of PBL at 40%, and the frequency of industry engagement activities averaged at five distinct interactions per academic session. The pre-and post- surveys assessed students’ employability skills, while feedback and participation metrics measured their engagement and satisfaction. The findings reveal a significant improvement in student employability skills, with an average increase of 25% in self-reported competencies in job-related skills. Implementing the I-PBL significantly increased student engagement by 30% and satisfaction by 35%, demonstrating the approach’s effectiveness. It is the first to bring industry-enriched PBL systematically into higher education. Based on these results, the endorsed new insights and enhancement strategies for student employability skills, as discussed in this book, will help bridge the gap between academic preparation and workforce demands. The study addresses the gap in current educational practices by presenting a detailed, empirically validated framework that educators and policymakers can implement to prepare students for the evolving demands of the workforce.